Dihydropyridine Calcium Channel Blockers Suppress the Transcription of PD-L1 by Inhibiting the Activation of STAT1 - Pan, Xiaohui; Li, Run; Guo, Hongjie; Zhang, Wenxin; Xu, Xiaqing; Chen, Xi; Ding, Ling (Frontiers in Pharmacology, 2021)
Programmed death ligand 1 (PD-L1) which is upregulated in various epithelial tumors, plays a central role in the evasion of the immune system. In addition to monoclonal antibodies that blocking PD1/PD-L1 axis, finding small molecule compounds that can suppress PD-L1 expression might be another substitutable strategy for PD1/PD-L1 based therapy. Here, we found that dihydropyridine calcium channel blockers dose-dependently reduced the expression of PD-L1, both in the cytoplasm and cell surface. IFNγ induced PD-L1 transcription was consistently suppressed by Lercanidipine in 24 hours, whereas, the half-life of PD-L1 protein was not significantly affected. IFNγ trigged significant STAT1 phosphorylation, which was eliminated by Lercanidipine. Similarly, STAT1 phosphorylation could also be abolished by extracellular calcium chelating agent EGTA and intracellular calcium chelator BAPTA-AM. Furthermore, Lercanidipine enhanced killing ability of T cells by down-regulating PD-L1. Taken together, our studies suggest that calcium signal is a crucial factor that mediates the transcription of PD-L1 and regulation of calcium can be used as a potential strategy for PD-L1 inhibition.